Behold it is I: scripture, tradition, and science on the real presence of Christ in the Eucharist - Trasancos, Stacy A. (TAN Books, 2021)
"The Catholic Faith begins and ends with Jesus Christ, culminating in the Eucharist as its Source and Summit. "Behold, it is I," Jesus says, and the faithful believe. Examining these words of Jesus, Fr. George Elliott and Dr. Stacy Trasancos provide some of the most convincing proofs for the Real Presence of Christ in the Eucharist from Scripture, Tradition, and the scientific investigation of Eucharistic miracles. In three sections, they walk readers through: A holistic and contextual reading of the Bible which points to the words of Christ at the Last Supper: "This is my body," and "This is my blood," How the Church Fathers handed on the teachings of the Apostles to the early Church in the centuries following Christ's earthly ministry. How the data from the investigation of Eucharistic miracles begs the ultimate question of the certainty of faith. Do we need Eucharistic miracles to prove that Jesus is truly present in the Eucharist? Should our certainty of faith be contingent upon Eucharistic miracles? The reader may be joyfully surprised at where the journey of this book will lead you, from the burning faith of the saints all the way back to Christ in the Gospels. It plainly sets forth the reality that the Eucharist is the Body of Christ. Just as in Biblical times, Jesus in the Blessed Sacrament is not a ghost and not a myth, but flesh and bone, hands and feet. "Behold," He said, "It is I.""--